Skin Cancer Risks Avoided by the Montreal Protocol—Worldwide Modeling Integrating Coupled Climate‐Chemistry Models with a Risk Model for UV. (26th September 2012) - van, Arjan; Slaper, Harry; den Outer, Peter N.; Morgenstern, Olaf; Braesicke, Peter; Pyle, John A.; Garny, Hella; Stenke, Andrea; Dameris, Martin; Kazantzidis, Andreas; Tourpali, Kleareti; Bais, Alkiviadis F.
Abstract The assessment model for ultraviolet radiation and risk "AMOUR" is applied to output from two chemistry‐climate models (CCMs). Results from the UK Chemistry and Aerosols CCM are used to quantify the worldwide skin cancer risk avoided by the Montreal Protocol and its amendments: by the year 2030, two million cases of skin cancer have been prevented yearly, which is 14% fewer skin cancer cases per year. In the "World Avoided, " excess skin cancer incidence will continue to grow dramatically after 2030. Results from the CCM E39C‐A are used to estimate skin cancer risk that had already been inevitably committed once ozone depletion was recognized: excess incidence will peak mid 21st century and then recover or even super‐recover at the end of the century. When compared with a "No Depletion" scenario, with ozone undepleted and cloud characteristics as in the 1960s throughout, excess incidence (extra yearly cases skin cancer per million people) of the "Full Compliance with Montreal Protocol" scenario is in the ranges: New Zealand: 100–150, Congo: −10–0, Patagonia: 20–50, Western Europe: 30–40, China: 90–120, South‐West USA: 80–110, Mediterranean: 90–100 and North‐East Australia: 170–200. This is up to 4% of total local incidence in the Full Compliance scenario in the peak year.